OPTIMASI OVERALL THERMAL TRANSFER VALUE (OTTV) PADA MASJID BAITURROHMAN DI JEMBER DENGAN PEMILIHAN KACA - Auryn Lusida Amir; Indah Sari Zulfiana (Jurnal Teknologi Terpadu, 2026)
The Overall Thermal Transfer Value (OTTV) is a parameter used to evaluate the thermal performance of building envelopes in controlling heat transfer due to conduction and solar radiation. Solar radiation from glass elements can increase the heat load in mosque spaces that have relatively large openings and large volumes. Therefore, optimising glass materials is an important strategy for improving the energy efficiency and thermal comfort of buildings in tropical environments. This study aims to determine the OTTV value of the Baiturrohman Mosque in Jember using building design documents and SNI 6389:2020 requirements. In addition, this study also investigates how the type of glass selected affects the reduction in OTTV value. The method used is quantitative-qualitative, and the experimental case study method is used to compare two types of glass in the same building configuration. The variables analysed include the thermal transmittance (U-value) and shading coefficient (SC) of the glass as the main parameters that affect the amount of heat radiation entering through the façade.The calculation results show that the use of 5 mm clear glass with a U-value of 5.8 W/m²K and SC 0.97 produces an OTTV value of 36.64 W/m². Next, a material substitution was carried out using Panasap Blue Green glass with a U-value of 5.8 W/m²K but an SC of 0.67. This change resulted in an OTTV value of 30.58 W/m². There was a decrease of 6.06 W/m² or about 16.54% compared to the initial condition. This decrease shows that the reduction in the SC value directly contributes to the reduction of solar heat radiation entering through the building envelope, even though the thermal conductivity value of the glass did not change. The results of this study prove that selecting the right type of glass can be an effective strategy in optimising the OTTV value of mosques without requiring structural changes to the building facade. This strategy is relevant for application in public buildings in tropical regions to support energy efficiency and improve the thermal comfort of worship spaces.